THE INFLUENCE OF TECHNOLOGY-BASED COMPETENCY DEVELOPMENT STRATEGY ON THE OPERATIONAL EFFICIENCY IN MULTINATIONAL COMPANIES - Khaeruman, Khaeruman; Dewi, Irma Nurmala; Sain, Zohaib Hassan (Yayasan Education and Social Center, 2025)
This study aims to analyze the effect of technology-based competency development (E-learning, Virtual Reality Training, and Mobile Learning) on ​​operational efficiency in multinational companies. Using a quantitative approach and descriptive-explanatory research design data were obtained through questionnaires and in-depth interviews from 90 employees involved in technology-based training programs in three multinational companies. E-learning, virtual reality training, and mobile learning were found to have a significant and positive impact on operational efficiency, as demonstrated by the study's findings. Training can be completed more quickly and at a lower cost with the help of e-learning technology. Virtual reality training offers a more realistic training experience, and mobile learning provides greater flexibility for learning. This study offers empirical evidence regarding technology's role in enhancing companies' operational efficiency. Multinational corporations can utilize this evidence to develop more effective and efficient competency development strategies